If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5t=6t+7
We simplify the equation to the form, which is simple to understand
5t=6t+7
We move all terms containing t to the left and all other terms to the right.
+5t-6t=+7
We simplify left and right side of the equation.
-1t=+7
We divide both sides of the equation by -1 to get t.
t=-7
| 599-5(21+20)=y | | 5(x+2)-3=12 | | 455=180+3x+1.5x | | 14+8x=-x-5 | | 4x^3-10x^2-64x+160=0 | | -3x+2x=5 | | -6=X+39/-9 | | 6x^2+5x=o | | 2-6(6+2k)=-106 | | -5r-(42+14r)=-99 | | 4x^3-10x^2-64+160=0 | | 163=-7x+3(7x+17) | | 9/3*3+7-3=y | | 3.5p=39.5 | | 2(4x+1)=4x-6 | | 8x-11=13+8u | | 3(x+2)-3x=12 | | 83=-5x+3(-3x-5) | | (3/7)*p=48 | | 1.4h=1.8h+4.8-.4h | | 4+-22= | | (X+2)+(2x+2x)=4x+x | | 2(2-4n)=28 | | -50=2x-7(x+15) | | -25-5= | | x+3.4=6.9 | | -5x+4(3x-10)=-82 | | -3x-4=4+10 | | 6-5t=4+3t | | 10x^2+y^2=110 | | 3p+9-2p=11-7 | | [7*(8+8)]+9=y |